Danos de níveis de infestação de Euschistus heros (Fabricius, 1798) e do Dichelops melacanthus (Dallas, 1851) (Heteroptera: pentatomidae) na fase inicial e impacto no desenvolvimento do milho - Istchuk , Ademar Novais (2020)
Pentatomids in corn has been observed over the last two decades. However, the overall increase of stink bugs importance in corn production is mostly a consequence of no-tillage system, growing two crops a year, corn immediately planted following soybean harvest due early maturity group soybeans, and the use of biotechnology for Lepidopteran control. The potential damage of these species to corn plants is still limited, especially under high population per plant. The present work aimed to compare the damage caused by two stink bugs species (Euschistus heros and Dichelops melacanthus) in early stage corn, at different infestation rates. The experiment was carried out under greenhouse conditions, with four infestation rates (zero, two, four and eight adults per plant) using field collected insects kept in cages until infestation date. Screened cages with four plants were infested at V1 growth stage, and the insects kept with the plants for 21 days. After this period, the cages were removed, and the surviving plants conducted until harvest. Five weekly evaluations were carried out, seven, 14, 21, 28 and 35 days after infestation. Injury scores, plant height until the last expanded leaf and stem diameter were measured in individual plants. After flowering, plant and ear height were measured. At physiological maturity were main cob length, number of grain rows per cob, number of grains per row, weight of 1000 grains and grain production per plot, adjusted to 13% moisture. The obtained data were submitted to variance analysis and compared using the Tukey’s test (P ≤ 0.05). Regression models were adjusted based on statistical significance. The stink bug D. melacanthus presented a higher damage severity in the initial phase of the corn crop when compared to the damage caused by E. heros, in all evaluations and infestation rates. Two adults of D. melacanthus per plant for 21 days caused the death of 96% of the corn plants, resulting in no grain production. The number of kernels per row and grain production was affected by the initial damage caused by E. heros. Each brown stink bug per plant was responsible for a 4% reduction in the total grain mass. Although brown stink bug can cause damage to early stage corn plants, a population four times larger was not enough to be compared with the damage caused by the green belly stink bug (D. melacanthus) in corn. The damage caused by one E. heros per plant reduced the number of grains per row and harvested grain weight in 11% in greenhouse condition.